On the estimation of the functional - Puriuškis, Gintaras (Lietuvos matematikos rinkinys, 2007)
There is considered the functionalinf(sup|f (i)(t)),The supremum is taken by i = 0, 1, 2, the infimum is taken by the function set KC2([0, 1]), with boundary conditionsf (0) = 1,  f'(0) = 1,  f (1) = 0,  f'(1) = 0.
Keywords: Schrödinger equations; boundary problem; Pontriagin’s problem